(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The internet and social media provide young people with a range of benefits, and opportunities to empower themselves in a variety of ways. Young people can maintain social connections and support networks that otherwise wouldn’t be possible, and can access more information than ever before. The communities and social interactions young people form online can be invaluable for bolstering and developing young people’s self-confidence and social skills.